Information dissemination of subak culture as a knowledge preservation effort in Museum Subak Bali - Ni Made Lila Sri Kamala; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This study aims to examine the information dissemination process implemented by Museum Subak. Dissemination is carried out to anticipate the low literacy of the community towards the values ​​of Subak culture and trigger a shift in the function of agricultural land into a tourism area that can threaten the sustainability of the Subak system as a local cultural heritage. Research Methods. This study uses a qualitative method with a case study approach and data collection through direct observation, interviews with selected informants, and analysis of documents related to activities at the Museum Subak. Data Analysis. Data analysis techniques used open coding, axial coding, and selective coding. Results. The results of this study are based on the SECI Model. These findings indicate the need for more adaptive, multilingual, and contextual strategies so that the transformation of Subak cultural knowledge can take place effectively and sustainably. Conclusion. This study found that dissemination activities at the Museum Subak primarily focused on the internalization process, namely the transformation of explicit knowledge into tacit knowledge through direct involvement of participants in learning activities. The research suggests that that social media use shouldbe optimized as a digital-based dissemination tool.